Preparation method and application of MnCeNbTiOx catalyst for degrading NO by NH3-SCR

By preparing the MnCeNbTiOx catalyst, the problems of insufficient low-temperature activity and narrow operating temperature window of the existing NH3-SCR catalyst were solved, efficient NOx degradation was achieved, and strict NOx emission standards were met.

CN119793443AInactive Publication Date: 2025-04-11CHONGQING UNIV OF TECH

Patent Information

Application Number
CN202510079620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing NH3-SCR catalysts have defects in insufficient low-temperature activity and narrow operating temperature windows, and are difficult to meet increasingly stringent NOx emission standards.

Method used

By preparing the MnCeNbTiOx catalyst, using Mn as the active component, Ce and Nb as the additive, and combining Ti as the support, the molar ratio and preparation process are optimized to improve the low-temperature denitrification activity and operating temperature window of the catalyst.

Benefits of technology

The low-temperature denitrification activity of the catalyst is significantly improved, and the operating temperature window is widened to 98% NO conversion rate. The T80 operating temperature window is widened to 175-435℃, and it is also cheap and non-toxic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005248142820000051
    Figure BDA0005248142820000051
  • Figure BDA0005248142820000061
    Figure BDA0005248142820000061
  • Figure BDA0005248142820000062
    Figure BDA0005248142820000062
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a MnCeNbTiOx catalyst for degrading NO by NH3-SCR (selective catalytic reduction), particularly relates to a catalyst for effectively degrading an atmospheric pollutant NO, and belongs to the field of atmospheric pollution treatment and environment-friendly catalytic environment. The catalyst is prepared by using Mn as a main active component, Ti as a carrier and transition metals Ce and Nb as auxiliaries through a coprecipitation method. The preparation method comprises the following steps: firstly, weighing an active component Mn (NO3) 2.4 H2O, an auxiliary agent Ce (NO3) 4.6 H2O and an auxiliary agent C10H5NbO20 according to a stoichiometric ratio, adding a proper amount of deionized water to completely dissolve, then adding a metered Ti (SO4) 2 carrier, stirring until the Ti (SO4) 2 carrier is completely dissolved, dropwise adding ammonia water under the condition of stirring to adjust the pH value to be approximately equal to 10, then stirring the obtained solution for 1 hour, aging for 1 hour, transferring into a centrifugal tube, centrifuging, washing to be neutral, and drying to obtain the catalyst. And placing the obtained catalyst sample in an oven at 110 DEG C for overnight drying, then taking out the dried catalyst sample, grinding the dried catalyst sample into powder, placing the powder in a muffle furnace, roasting the powder at 500 DEG C for 5 h, and naturally cooling the powder to obtain the MnCeNbTiOx catalyst. The MnCeNbTiOx catalyst disclosed by the invention has better low-temperature activity and a wider operating temperature window, can effectively remove NO in the tail gas of the industrial furnace, achieves the highest NO conversion rate of 98% at the temperature of 250 DEG C, and has a T80 operating temperature window of 175-435 DEG C. Meanwhile, characterization results show that after the auxiliaries Ce and Nb are added, the catalyst mainly presents an amorphous structure, the oxidation-reduction performance of the catalyst and the interaction force among the components are enhanced, and improvement of the denitration activity of the catalyst is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a MnCeNbTiO2 nanostructured carbon nanotube for NH3-SCR degradation of NO. x The invention relates to a preparation method and application of a catalyst, specifically, it is a catalyst for effectively degrading the air pollutant NO, and belongs to the field of air pollution control and environmental catalysis. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main pollutants in the atmosphere, mainly coming from waste gas emissions from fixed and mobile pollution sources. x It not only harms human health, but also produces photochemical smog, acid rain, greenhouse effect, and leads to environmental pollution such as ozone depletion. x The emission of pollutants is one of the important contents of current air pollution control.

[0003] NH3 selective catalytic reduction (NH3-SCR) technology has become an effective way to remove NO from flue gas from stationary and mobile sources. x NH3-SCR technology uses liquid ammonia or urea as the ammonia source, and selectively reacts with NO under the action of a catalyst. x The process of generating non-toxic and harmless N2 and H2O. The catalyst is the core of NH3-SCR technology, and the performance of the catalyst will directly affect the denitrification effect of the entire NH3-SCR system. x The development of catalysts is imperative.

[0004] Traditional commercial V2O5-WO3(MoO3) / TiO2 denitrification catalysts at home and abroad have poor low-temperature activity (<300℃), narrow operating temperature window (300-400℃), and vanadium species have defects such as biological toxicity and poor anti-toxicity, which limit their scope of use. Mn-based catalysts have excellent low-temperature SCR activity due to their variable valence states and excellent redox ability. They are non-toxic and low-priced, and are environmentally friendly SCR catalysts that can replace V-based catalysts. They have attracted widespread attention. However, single Mn-based catalysts still have disadvantages such as narrow operating temperature window and low activity at high temperature, which limits their practical application. Therefore, it is urgent to modify Mn-based catalysts and develop a low-cost, environmentally friendly NH3-SCR denitrification catalyst with better activity and a wider operating temperature window to meet the increasingly stringent NO x Emission standards.

[0005] The design idea of ​​this patent is to first screen out non-toxic Mn with good low-temperature activity and low cost as the metal active component. Based on the literature, the active component Mn content was first optimized, but its operating temperature window was narrow. The literature reports that adding additives can not only promote the high dispersion of active components but also strengthen the interaction between additives and active components and carriers, improve the denitrification activity of catalysts and widen the operating temperature window. Therefore, we have done a lot of exploratory work to screen additives according to the classification and structural characteristics of metals. According to literature reports, the introduction of Ce, Fe, Ni, Cu, Co, La and Mo additives can improve the low-temperature activity of catalysts and widen the operating temperature window, but the catalytic effects of Ce, Fe, Ni, Cu, Co, La and Mo additives are not satisfactory. It was thought that the special physical and chemical properties of Ce, Fe, Ni, Cu, Co, La and Mo additives should have higher low-temperature activity and wider operating temperature window, but they failed to show it. Summary of the invention

[0006] The present invention aims to provide a MnCeNbTiO2 nanocomposite for NH3-SCR degradation of NO. x The preparation method and application of the catalyst have the advantages of simple process, easy operation and low cost. x The catalyst significantly improves the low-temperature denitrification activity of the catalyst and broadens its operating temperature window. In addition, the catalyst is low-cost and non-toxic.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A MnCeNbTiO2 for NH3-SCR Degradation of NO x The method for preparing a catalyst comprises the following steps:

[0009] (a) Weigh the active component Mn(NO3)2·4H2O, the additive Ce(NO3)4·6H2O, and the additive C in the stoichiometric ratio. 10 H5B 20 Dissolve in deionized water and stir until completely dissolved to obtain a clear solution;

[0010] (b) adding a measured amount of Ti(SO4)2 carrier to the transparent solution obtained in step (a);

[0011] (c) adding aqueous ammonia dropwise to the solution of step (b) while stirring to adjust the pH value to 10;

[0012] (d) stirring the solution obtained in step (c) for 1 h and then aging for 1 h;

[0013] (e) transferring the solution obtained in step (d) into a centrifuge tube and centrifuging to wash until neutral;

[0014] (f) placing the sample catalyst obtained in step (e) in an oven at 110° C. and drying overnight;

[0015] (g) Grind the sample obtained in step (f) into fine powder, place it in a muffle furnace, and roast it for 5 hours to obtain MnCeNbTiO x catalyst.

[0016] According to the above scheme, the molar ratio of the carrier to the active component is n(Ti(SO4)2):n(Mn(NO3)2·4H2O)=1:0.05-0.2.

[0017] According to the above scheme, the molar ratio of the carrier to the auxiliary agent Ce is n(Ti(SO4)2):n(Ce(NO3)4·6H2O)=1:0.01-0.2.

[0018] According to the above scheme, the molar ratio of the carrier to the additive Nb is n(Ti(SO4)2):n(C 10 H5B 20 )=1:0.01-0.1.

[0019] According to the above scheme, the mass of Ti(SO4)2 is 3g;

[0020] Preferably, the drying temperature is 110°C;

[0021] The drying time is 12h;

[0022] The calcination temperature is 500°C;

[0023] The calcination time is 5 hours.

[0024] The present invention also provides the use of the NH3-SCR NO degradation catalyst prepared by the preparation method described in any one of the above technical solutions in tail gas denitrification.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. MnCeNbTiO for SCR NO degradation reaction provided by the present invention x The catalyst is inexpensive and non-toxic, has excellent low-temperature catalytic activity and a wide operating temperature window, and can achieve a maximum NO conversion rate of 98% at 250°C. 80 The operating temperature window is widened to 175-435°C.

[0027] 2. The preparation method has simple process, easy-to-control preparation conditions and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are catalytic activity test graphs of the catalysts prepared in Examples 1, 2, 3, 4 and 5.

[0029] Figure 2 These are the catalytic activity test graphs of the catalysts prepared in Examples 2, 6, 7, 8, 9 and 10.

[0030] Figure 3 These are the catalytic activity test graphs of the catalysts prepared in Examples 6, 11, 12, 13, 14 and 15.

[0031] Figure 4 The catalytic activity test diagrams of the catalysts prepared in Examples 2, 6 and 11.

[0032] Figure 5 XRD spectra of catalysts prepared in Examples 2, 6 and 11.

[0033] Figure 6 H2-TPR spectra of the catalysts prepared in Examples 2, 6 and 11.

[0034] Figure 7 XPS spectra of the catalysts prepared in Examples 2, 6 and 11. DETAILED DESCRIPTION

[0035] The present invention will be further described below through some implementation examples, but the present invention is not limited thereto.

[0036] Example 1TiO x Catalyst synthesis

[0037] Weigh 3g Ti(SO4)2, add 30ml deionized water and stir until completely dissolved, then add ammonia water dropwise while stirring to adjust pH≈10, stir for 1h, age for 1h, then transfer to a centrifuge tube for centrifugation, centrifuge and wash until neutral, dry the obtained precipitate in an oven at 110℃ for 12h, and finally calcine at 500℃ in a muffle furnace in an air atmosphere for 5h. The calcined powder is pressed into tablets with a tablet press at a pressure of 20Mpa and crushed into 20-40 meshes to obtain TiO x catalyst.

[0038] Catalyst Evaluation

[0039] The activity evaluation of the catalyst was carried out in a homemade continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6mm and a length of 33cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow is controlled by a mass flow meter. The reaction raw gas: 400ppm NH3, 400ppm NO, 3% O2 ​​and balance gas Ar. In the experiment, the catalyst dosage is 0.2g, the reaction temperature is 100℃~450℃, and sampling is performed every 50℃. The detection is carried out with a flue gas analyzer (MRU, VARIO PLUS) to calculate the conversion rate of NO. The NO conversion curve of the catalyst at different temperature points is shown in the figure below. Figure 1 shown.

[0040] Example 2Mn 0.1 TiO x Catalyst synthesis

[0041] The difference from Example 1 is that the active component Mn is added, as follows: 0.3138g of Mn(NO3)2·4H2O is weighed, 30ml of deionized water is added to dissolve it, and then 3g of Ti(SO4)2 is added. After the solution is completely dissolved, ammonia water is added dropwise while stirring to adjust the pH to 10, stirred for 1h, aged for 1h, and then transferred to a centrifuge tube for centrifugation, centrifuged and washed until neutral, the obtained precipitate is dried in an oven at 110°C for 12h, and finally calcined at 500°C in a muffle furnace in an air atmosphere for 5h. The calcined powder is pressed into tablets at a pressure of 20Mpa using a tablet press and crushed to 20-40 mesh, thus obtaining Mn 0.1 TiO x catalyst.

[0042] Catalyst Evaluation

[0043] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 1 The 100℃, 150℃, maximum NO conversion rate and T 80 The operating window temperature is shown in Table 2.

[0044] Embodiments 3 to 5

[0045] Compared with Example 2, only the active component content of the catalyst is different, and the other processes are the same as Example 2 to obtain the finished catalysts. The catalyst compositions of Examples 3 to 5 are shown in Table 1.

[0046] Catalyst Evaluation

[0047] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 1 The 100℃, 150℃, maximum NO conversion rate and T 80The operating window temperature is shown in Table 2.

[0048] Example 6Mn 0.1 Ce 0.1 TiO x Catalyst synthesis

[0049] The difference from Example 2 is that the first auxiliary agent Ce is added, as follows: weigh 0.3138g of Mn(NO3)2·4H2O, 0.5428g of Ce(NO3)2·6H2O, and 30ml of deionized water, mix and stir until dissolved; add 3g of Ti(SO4)2, and after it is completely dissolved, add ammonia water dropwise while stirring to adjust the pH to 10, stir for 1h, and then age for 1h, then transfer it to a centrifuge tube for centrifugation, centrifuge and wash until neutral, dry the obtained precipitate in an oven at 110°C for 12h, and finally roast it at 500°C in a muffle furnace in an air atmosphere for 5h. The roasted powder is pressed into tablets with a tablet press at a pressure of 20Mpa and crushed to 20-40 mesh, thus obtaining Mn 0.1 Ce 0.1 TiO x catalyst.

[0050] Catalyst Evaluation

[0051] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 The 100℃, 150℃, maximum NO conversion rate and T 80 The operating window temperature is shown in Table 2.

[0052] Embodiments 7 to 10

[0053] Compared with Example 6, only the content of the first catalyst additive Ce is different, and the other processes are the same as Example 5 to obtain various finished catalysts. The catalyst compositions of Examples 7 to 10 are shown in Table 1.

[0054] Catalyst Evaluation

[0055] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 The 100℃, 150℃, maximum NO conversion rate and T 80 The operating window temperature is shown in Table 2.

[0056] Example 11Mn 0.1 Ce 0.1 Nb 0.03 TiO x Catalyst synthesis

[0057] The difference from Example 6 is that a second additive Nb is added, specifically as follows: 0.3138 g of Mn(NO3)2·4H2O, 0.5428 g of Ce(NO3)2·6H2O, 0.2018 g of C 10 H5B 20 , 30ml deionized water, stir and mix until dissolved, add 3g Ti(SO4)2, after complete dissolution, add ammonia water dropwise while stirring to adjust pH≈10, stir for 1h, age for 1h, then transfer to a centrifuge tube for centrifugation, centrifuge and wash until neutral, dry the obtained precipitate in an oven at 110℃ for 12h, and finally roast at 500℃ in a muffle furnace in an air atmosphere for 5h. The roasted powder is pressed into a tablet press at a pressure of 20Mpa and crushed to 20-40 mesh, thus obtaining Mn 0.1 Ce 0.1 Nb 0.03 TiO x catalyst.

[0058] Catalyst Evaluation

[0059] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 3 The 100℃, 150℃, maximum NO conversion rate and T 80 The operating window temperature is shown in Table 2.

[0060] Embodiments 12 to 15

[0061] Compared with Example 11, only the content of the second promoter Nb in the catalyst is different, and the other processes are the same as Example 10 to obtain the finished catalysts. The catalyst compositions of Examples 12 to 15 are shown in Table 1.

[0062] Catalyst Evaluation

[0063] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 3 The 100℃, 150℃, maximum NO conversion rate and T 80 The operating window temperature is shown in Table 2.

[0064] Example Metal Oxide Catalyst Composition Table:

[0065] The composition of the metal oxide catalyst in the specific embodiment is shown in Table 1:

[0066] Activity evaluation results:

[0067] The specific activity evaluation results are shown in Table 2:

[0068] XRD characterization

[0069] Figure 5 In the analysis of TiO x , Mn 0.1 TiO x , Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x XRD spectrum of the sample. It can be seen from the figure that TiO x The catalyst only has anatase-type TiO2 peak. 0.1 TiO x The catalyst has two TiO2 peaks, anatase and spinel, and no Mn crystal form is detected, indicating that the Mn component exists in an amorphous form. 0.1 Ce x TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x In the spectrum of the catalyst, no X-ray diffraction peak of an obvious phase was observed, which means that there is no relatively complete crystal form in the catalyst, and the internal structure of the catalyst is amorphous. At this time, the interaction between Mn, Ce, Nb, and Ti elements inhibits the formation of crystals, thereby promoting the improvement of the catalytic activity of the catalyst. Therefore, after adding the additives Ce and Nb, the Mn 0.1 Ce 0.1 Nb 0.03 TiO x The catalyst showed better low-temperature activity and a wider temperature operating window.

[0070] TPR characterization

[0071] The reducible species in the catalyst are crucial for the completion of the redox cycle in the NH3-SCR reaction. Figure 6 H2-TPR results for three different catalysts are shown. In the temperature range of 100-800 °C, Mn 0.1 TiO x Three peaks were fitted in the H2-TPR diagram of the catalyst: Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiOx Four peaks were fitted in the H2-TPR diagram of the catalyst. The low-temperature reduction peaks at 344°C, 402°C and 430°C were attributed to the reduction of MnO2→Mn2O3, the reduction peaks at 463°C, 495°C and 505°C were attributed to the reduction of Mn2O3→Mn3O4, the reduction peaks at 477°C, 512°C and 538°C were attributed to the reduction of Mn3O4→MnO, and the reduction peaks at 572°C and 585°C were attributed to Ce. 4+ →Ce 3+ By comparison, it can be found that compared with the basic Mn 0.1 TiO x Compared with the catalyst, the Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x The reduction peak of the catalyst gradually moves toward the high temperature direction. This change may be caused by the interaction between the components in the catalyst after the introduction of the additives Ce and Nb, which in turn promotes the improvement of the catalytic activity of the catalyst. 0.1 Ce 0.1 Nb 0.03 TiO x This is one of the reasons why the catalyst exhibits excellent denitrification activity.

[0072] XPS characterization

[0073] The Mn 0.1 TiO x , Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x The chemical state of the surface species of the catalyst. Figure 7 The characteristic peaks of Mn 2p, Ce 3d, Ti 2p, O 1s and Nb 3d in the three catalysts are shown. Figure 7 (a) shows the Mn 2p spectrum of the catalyst. It can be seen from the figure that after the introduction of additives Ce and Nb, the Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x Mn of catalyst 2+ and Mn4+ The shift to lower binding energy indicates that the chemical state of the active component Mn in the catalyst modified by Ce and Nb doping has changed, the electron cloud density of the Mn species in the catalyst has increased, and the interaction force between the components has been enhanced. Figure 7 (b) shows the Ce 3d spectrum of the catalyst. It can be seen from the figure that after the introduction of the additive Nb, the Mn 0.1 Ce 0.1 Nb 0.03 TiO x Ce of catalyst 3+ and Ce 4+ The shift to lower binding energy indicates that the chemical state of Ce in the catalyst modified by Nb doping has changed, the electron cloud density of Ce species in the catalyst has increased, the chemical environment around Ce species in the catalyst has changed, and the interaction force between the components has been enhanced. Figure 7 (c) shows the Ti 2p spectrum of the catalyst. 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x The peak of the catalyst shifts toward low binding energy, indicating that the chemical state of Ti in the catalyst modified by Ce and Nb doping has changed, the electron cloud density of Ti species in the catalyst has increased, the chemical environment around Ti species in the catalyst has changed, and the interaction force between the components has been enhanced. Figure 7 (d) shows the O1s spectrum of the catalyst. It can be observed from the figure that after adding Ce and Nb additives, Mn 0.1 Ce 0.1 TiO x and Mn 0.1 Ce 0.1 Nb 0.03 TiO x The peak of the catalyst shifts to a lower binding energy, indicating that the Ce and Nb-doped catalysts increase the O β and O α The electron cloud density changes the chemical environment around the O species in the catalyst. Figure 7 (e) shows the Nb 3d spectrum of the catalyst. The combined energy of these two peaks indicates that Nb 5+ exists in the form of.

Claims

1. A MnCeNbTiO for NH3-SCR NO degradation x The preparation method and application of the catalyst, the preparation method comprises the following steps: (a) Weigh the active component Mn(NO3)2·4H2O, the additive Ce(NO3)4·6H2O, and the additive C in the stoichiometric ratio. 10 H5B 20 Dissolve in deionized water and stir until completely dissolved to obtain a clear solution; (b) adding a measured amount of Ti(SO4)2 carrier to the transparent solution obtained in step (a); (c) adding aqueous ammonia dropwise to the solution of step (b) while stirring to adjust the pH value to 10; (d) stirring the solution obtained in step (c) for 1 h and then aging for 1 h; (e) transferring the solution obtained in step (d) into a centrifuge tube and centrifuging to wash until neutral; (f) placing the sample catalyst obtained in step (e) in an oven at 110° C. and drying overnight; (g) Grind the sample obtained in step (f) into fine powder, place it in a muffle furnace, and roast it for 5 hours to obtain MnCeNbTiO x catalyst.

2. The MnCeNbTiO for NH3-SCR degradation of NO according to claim 1 x A method for preparing a catalyst, characterized in that: The molar ratio of the carrier to the active component is n(Ti(SO4)2):n(Mn(NO3)2·4H2O)=1:0.05-0.

2.

3. The MnCeNbTiO for NH3-SCR degradation of NO according to any one of claims 1 to 2 x A method for preparing a catalyst, characterized in that: The molar ratio of the carrier to the auxiliary agent Ce is n(Ti(SO4)2):n(Ce(NO3)4·6H2O)=1:0.01-0.

2.

4. MnCeNbTiO for NH3-SCR degradation of NO according to any one of claims 1 to 3 x A method for preparing a catalyst, characterized in that: The molar ratio of the carrier to the additive Nb is n(Ti(SO4)2):n(C 10 H5B 20 )=1:0.01-0.

1.

5. MnCeNbTiO for NH3-SCR degradation of NO according to any one of claims 1 to 4 x A method for preparing a catalyst, characterized in that: The carrier precursor is Ti(SO4)2.

6. Use of any one of the catalysts for NH3-SCR degradation of NO according to any one of claims 1 to 5 in exhaust gas denitration.

Citation Information

Patent Citations

  • Low-temperature denitration catalyst MnOx-CeO2-TiO2-Al2O3, and preparation method and application thereof

    CN103433033A

  • Manganese based SCR catalyst for low temperature denitration and preparation method thereof

    CN105363434A

Cited By

  • Preparation method and application of amorphous low-temperature denitration catalyst capable of resisting water and ammonium bisulfate poisoning

    CN121972159A